Complex formation and enantioselectivity studies of triazole fungicide and organophosphorus pesticide enantiomers using capillary electrophoresis - Wan Ibrahim, Wan Aini; Sanagi, Mohd. Marsin; Hermawan, Dadan (Faculty of Science, 2008)
Several cyclodextrin modified-micellar electrokinetic chromatography (CDMEKC) methods were developed for the successful triazole fungicides separation. In the first part, an efficient method was developed for the simultaneous enantioseparation of cyproconazole (4 stereoisomer), bromuconazole (4 stereoisomer) and diniconazole (2 stereisomer) enantiomers using CD-MEKC with a dual mixture of neutral cyclodextrins as chiral selector. The best simultaneous separation of cyproconazole, bromuconazole, and diniconazole enantiomers was achieved with a mixture of 27 mM HP-Î²-CD and 3 mM HP-Î³-CD in 25 mM phosphate buffer (pH 3.0) containing 40 mM sodium dodecyl sulfate (SDS) and 15% iso-propanol as organic modifier. Complete separation of 10 stereoisomer of triazole fungicides were obtained in a single run with good resolution (Rs 1.74“26.31) and high peak efficiency (N > 400 000). In the second part of the study, enantioseparation of hexaconazole, penconazole, myclobutanil, and triadimefon was investigated. Simultaneous enantioseparation of penconazole, myclobutanil, and triadimefon was achieved under acidic condition (pH 3.0) using 25 mM phosphate buffer, 50 mM SDS, and 30 mM HP-Î³-CD, with Rs greater than 0.9 whereas, simultaneous enantioseparation of hexaconazole, penconazole, and myclobutanil was successfully achieved under neutral condition (pH 7.0) using 25 mM phosphate buffer, 40 mM SDS, and 40 mM HP-Î³-CD, with Rs greater than1.6. In order to improve detection sensitivity, on-line preconcentration technique was investigated. It was found that sweeping technique as an on-line preconcentration technique improved the detection sensitivity of the enantioseparation of cyproconazole, bromuconazole, and diniconazole by 30 to 60-fold, with good repeatabilities in the migration time, peak area and peak height were obtained with RSDs in the range of 0.08“0.32%, 0.03“ 2.44%, and 2.13“8.44% respectively. Furthermore, sweeping technique improved the detection sensitivity of the enantioseparation of hexaconazole, penconazole and myclobutanil by 62- to 67-fold. Good repeatabilities in the migration time, peak area and peak height were obtained with RSDs in the range of 2.39“3.90%, 1.96€“6.15%, and 2.80“6.64% respectively. Finally, the formation constant of diniconazole enantiomers with HP-Î³-CD under neutral and acidic condition was investigated using CD-MEKC.